Strongly prime submodules and strongly 0-dimensional modules - Bilgin, Zehra; Koc, Suat; Ozkirisci, Neslihan Aysen (LUHANSK TARAS SHEVCHENKO NATL UNIV, 2019)
In this work, we study strongly prime submodules and strongly 0-dimensional modules. We give some equivalent conditions for being a strongly 0-dimensional module. Besides we show that the quasi-Zariski topology on the spectrum of a strongly 0-dimensional module satisfies all separation axioms and it is a metrizable space.
Keywords: strongly prime submodule; strongly 0-dimensional module; multiplication module; quasi-Zariski topology; Mathematics